In Vitro Activities of Voriconazole, Itraconazole, and Amphotericin B against Blastomyces dermatitidis, Coccidioides immitis, and Histoplasma capsulatum - Li, Ren-Kai (American Society for Microbiology, 2000)
The in vitro activity of voriconazole was compared to those of itraconazole and amphotericin B against the mold forms of 304 isolates of three dimorphic fungi, Blastomyces dermatitidis, Coccidioides immitis, and Histoplasma capsulatum. MICs were determined by a broth microdilution adaptation of the National Committee for Clinical Laboratory Standards M27-A procedure. RPMI 1640 medium was used for tests with voriconazole and itraconazole, whereas Antibiotic Medium 3 with 2% glucose was used for amphotericin B. Minimum fungicidal concentrations (MFCs) were also determined. Amphotericin B was active against all three dimorphic fungi, with MICs at which 90% of the isolates tested are inhibited (MIC(90)s) of 0.5 to 1 μg/ml. Itraconazole had MIC(90)s of 0.06 μg/ml for H. capsulatum, 0.125 μg/ml for B. dermatitidis, and 1 μg/ml for C. immitis. The MIC(90)s of voriconazole were 0.25 μg/ml for all three fungi. Amphotericin B was fungicidal for B. dermatitidis and H. capsulatum with MFCs at which 90% of strains tested are killed (MFC(90)s) of 0.5 and 2 μg/ml, respectively. It was less active against C. immitis, with MFCs ranging from 0.5 to >16 μg/ml. Voriconazole and itraconazole were lethal for most isolates of B. dermatitidis, with MFC(50)s and MFC(90)s of 0.125 and 4 μg/ml, respectively. Both azoles were fungicidal for some isolates of H. capsulatum, with MFC(50)s of 2 and 8 μg/ml for itraconazole and voriconazole, respectively; neither had a lethal effect upon C. immitis. Our results suggest that voriconazole possesses promising activity against these important human pathogens.